Rhodotorula mucilaginosa, a carotenoid producing yeast strain from a Patagonian high-altitude lake - Libkind, D; Brizzio, S; van Broock, M (Folia microbiologica, 2004)
The red yeast Rhodotorula mucilaginosa strain CRUB 0138 (previously identified as R. lactosa) was isolated from a high-altitude Patagonian Lake Toncek (1700 m a.s.l.), and assigned with mucilaginosa species. Its biochemical, physiological and molecular features were assessed and compared to R. mucilaginosa PYCC 5166 type strain using a polyphasic approach; in addition, biomass and carotenoid pigment production at different C/N ratios were determined in an incubator shaker. Phenetic characterization by means of 70 current physiological tests including assimilation of aldaric acids and aromatic compounds, and also the ability to grow with amino acids as sole carbon sources, was carried out. According to numerical taxonomy calculations, similarity indexes between R. mucilaginosa CRUB 0138 and PYCC 5166 type strain were 0.86 and 0.77, corresponding to a complete set of physiological tests and MSP-PCR (Mini/Micro Satellite Primed PCR; (GTG)5, M13 and (GAC)5 primers were employed) fingerprinting. Killer activity against 2 native strains, Rhodosporidium kratochvilovae and R. mucilaginosa was detected. Maximum biomass-glucose conversion efficiency (87%) and maximum carotenoid yield (2.32 mg/L) were obtained at C/N = 5 in culture medium containing 10 and 40 g/L glucose, respectively. Different C/N ratios did not influence carotenoid pigment production but low C/N enhanced biomass yield.
Keywords: Polymerase Chain Reaction; dusík; DNA, Fungal; Argentina; karotenoidy; mikrobiologie vody; mykologické určovací techniky; sladká voda; antibióza; biologické pigmenty; Glucose; polymerázová řetězová reakce; Biomass; Mycological Typing Techniques; Carbon; DNA Fingerprinting; Basidiomycota; Microsatellite Repeats; Fresh Water; Water Microbiology; DNA fungální; Pigments, Biological; Antibiosis; Carotenoids; Nitrogen; biomasa; uhlík; DNA fingerprinting; Rhodotorula; mikrosatelitní repetice; glukosa